O lugar do outro nas intolerâncias: raça, etnia e gênero como marcadores nas (in)expressões de fé e religiosidade = The place of others in intolerances : race, ethnicity and gender as markers in (in)expressions of faith and religiosity - Albuquerque, Kristine Kelly de (Ciencias sociales y religión, 2020)
The present work aims to reflect on race, ethnicity and gender, in an intersectional way, and their repercussions on religious representations and experiences, both individually and collectively. The importance of the theme lies in the fact that the categories mentioned, when related to social identities, manifest specific forms of discrimination, and is therefore essential for critical sociocultural analysis. Moreover, studies on religious practices within the social sciences reveal important aspects of the social representations marked by power-legitimating discourses that are present in everyday relations and practices of rights violations. Thus, the proposal launched is to analyze how these categories have repercussions on the practices of two specific religions, namely those belonging to the African matrix and Islam. For this, a sociohistorical perspective of both religions will be presented, as well as the conceptual definitions of the analyzed categories. Finally, we will present the interactive effects of these on religious experiences.